Control of Lesion Nematodes, Pratylenchus spp., in Grapevine Nursery Material by Immersion in Fenamiphos Solutions and Hot Water - Loubser, J.T.; Hoppner, G.F.J. (South African Journal of Enology and Viticulture, 2017)
Control of Pratylenchus spp. in dormant grapevine nursery material was attempted using fenamiphos solutions and a hot-water treatment. Five months after treatment, the lesion nematodes were eradicated by all treatments. Although no visual phytotoxicity symptoms were recorded at any stage wiith any of the treatments tested, hot water significantly reduced plant growth of certain scion/rootstock combinations. Treatment with 0,1 % (a.i.) fenamiphos solution for 30 minutes at 25°C is recommended.